Particulate Air Pollution at Schools: Indoor-Outdoor Relationship and Determinants of Indoor Concentrations - Mohammadyan, Mahmoud; Alizadeh-Larimi, Ahmad; Etemadinejad, Siavash; Latif, Mohd Talib; Heibati, Behzad; Yetilmezsoy, Kaan; Abdul-Wahab, Sabah Ahmed; Dadvand, Payam (TAIWAN ASSOC AEROSOL RES-TAAR, 2017)
This study aimed to assess the relationship between indoor and outdoor particulate air pollution at primary schools, and identify the determinants of indoor pollution concentrations. The study was conducted in six classrooms within six primary schools in Sari, Northern Iran. Indoor concentrations of particulate matter (PM) with an aerodynamic diameter of less than 10 mu m (PM10), 2.5 mu m (PM2.5), and 1 mu m (PM1.0) were assessed in classrooms, and outdoor concentrations of PM2.5 on the school playgrounds were monitored simultaneously by using two real-time and portable dust monitors during autumn, winter, and spring, yielding 26 sampling days for each school in total. The highest outdoor and indoor PM2.5 concentrations were found in winter and spring, respectively. The mean indoor PM2.5 concentration (46.9 +/- 32.9 mu g m(-3)) was higher than that measured outdoors (36.8 +/- 33.2 mu g m(-3)). Indoor PM2.5 and PM1.0 were moderately correlated with outdoor PM2.5 concentrations, which was the main determinant for all indoor particulate concentrations, however, a distinct pattern was observed for PM10 and PM2.5 compared to PM1.0. While meteorological variables (i.e., ambient temperature, relative humidity) could predict indoor PM10 and PM2.5 concentrations, the total area of the windows and the number of students in a classroom were predictors for PM1.0 levels. The findings of this study could inform policy makers in implementing evidence-based targeted interventions aimed at reducing air pollution in school settings.
Keywords: Classrooms; Particulate matter; PM2.5; PM10; Iran; EXPOSURE; MATTER; BARCELONA; HOME; Environmental Sciences & Ecology